Dyslipidaemia after switch to tenofovir alafenamide (TAF)‐based cART regimens in a cohort of HIV‐positive patients: what clinical relevance?. Issue 2 (21st October 2020) - Gazzola, L; Tagliaferri, G; De Bona, A; Mondatore, D; Borsino, C; Bini, T; Marchetti, G; d'Arminio Monforte, A
Abstract : Objectives: Switching from tenofovir (TDF) to tenofovir alafenamide (TAF) affects lipid profile. The aim of this study was to evaluate whether this results in an increased frequency of patients with low‐density lipoprotein (LDL) above their cardiovascular‐related target. Methods: All HIV patients switching from TDF to TAF, with no changes of the anchor drug, and with plasma lipids available within 6 months before and after the switch, were included. Demographic, HIV‐related parameters, cardiovascular (CV) risk factors and lipid profile on both TDF and TAF were collected. The CV risk score and the relative target of LDL for each patient were calculated according to 2016 European Society of Cardiology/European Atherosclerosis Society (ESC/EAS) guidelines for the management of dyslipidaemias. Modifications in lipid profiles and in the prevalence of patients with LDL above their CV‐related target were evaluated after switch to TAF. Results: Overall, 221 HIV patients were included, according to CV risk: 55% at low risk, 34% at moderate risk, and 11% at high/very high risk. By analysing lipid profiles according to CV risk, 38% of patients on TDF had LDL above their CV target; this prevalence increases to 60% after switching to TAF ( P  < 0.0001). The presence of cobicistat in the combination antiretroviral therapy (cART) regimen was associated with an increased risk of LDL above the CV‐related target after switch to TAF [adjusted odds ratio (aOR) = 2.4, 95% confidence interval (CI): 1–5.1], P  = 0.03) and with an increased prescription of lifestyle/therapeutic intervention (OR = 3.0, 95% CI: 1.7–5.3, P  < 0.0001). Discussion: Switching from TDF to TAF affects lipid parameters, and data from real life suggest a clinical relevance of this worsening that often leads clinicians to implement lifestyle/therapeutic interventions.